2017
DOI: 10.1007/s11325-017-1486-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and inflammation indicate significant differences in the severity of obstructive sleep apnea within similar apnea-hypopnea index groups

Abstract: These data suggest that increased hypoxia severity may mediate increased inflammation and activation of platelets and contribute to the pathogenesis of WMH in patients with OSA. In addition, patients with severe OSA may show significant variability in inflammation and vascular risk. Further prospective data are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…40 In addition, SDB, hypoxemia and inflammation were associated with WMH in people with SDB. 41 In contrast, some studies indicate a lack of association between SDB and WMH. For instance, in a study of hypertensive patients, researchers did not find that severity of SDB was associated with white matter disease based on a visual rating scale.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, SDB, hypoxemia and inflammation were associated with WMH in people with SDB. 41 In contrast, some studies indicate a lack of association between SDB and WMH. For instance, in a study of hypertensive patients, researchers did not find that severity of SDB was associated with white matter disease based on a visual rating scale.…”
Section: Discussionmentioning
confidence: 99%
“…Lowest oxygen saturation is known to be well correlated with the severity of OSA, as measured by the AHI [ 16 ]. However, AHI was not significantly changed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanisms of OSAS are hypoxia and oxidative stress; however, several studies have demonstrated that inflammation also plays a crucial role in the occurrence and development of OSAS [ 14 ]. Systemic and local inflammation in OSAS patients manifests as a result of chronic intermittent hypoxemia (CIH) [ 11 , 15 ], snoring [ 16 ], continuous hypoxia [ 17 ], oxidative stress, and sleep fragmentation and deprivation [ 18 20 ]. In the last two decades, many studies have investigated the precise interactions between OSAS and inflammation in both adults and children, and some studies have tried to elucidate the potential biomarkers in the presence of OSAS and OSAS-related morbidities [ 21 23 ].…”
Section: Inflammation In Osasmentioning
confidence: 99%